PENGARUH SERTIFIKASI DAN KESEJATERAAN GURU TERHADAP KINERJA GURU DALAM PROSES PEMBELAJARAN (STUDI DI YAYASAN MIFTAHUL HUDA KEPANJEN) - Rifqi Rahmat Raharjo; Agus Widarko; Afi Rachmat Slamet (UNIVERSITAS ISLAM MALANG, 2017)
ABSTRACTThis study aims to determine the effect of certification on the performance of teachers in the learning process, knowing the influence of teacher welfare on teacher performance in the learning process. The location of this research is at Jl. Pesantren III Mojosari Kepanjen Malang post code 65163, Mojosari Village, Kepanjen District, Malang Regency. Samples taken as many as 32 respondents. Data collection methods used were questionnaires and interviews. Data analysis method used is quantitative method that is by using Multiple Linear Regression Analysis. The results of this study indicate that the certification has a positive influence on teacher performance in the learning process at Miftahul Huda Kepanjen foundation, teacher welfare has a positive influence on teacher performance in the learning process at Yayasan Miftahul Huda Kepanjen.Keywords: Certification, teacher welfare, teacher performance in learning process.